NF-κB in monocytes and macrophages – an inflammatory master regulator in multitalented immune cells - Mussbacher, Marion; Derler, Martina; Basílio, José; Schmid, Johannes A. (Frontiers in Immunology, 2023)
Nuclear factor κB (NF-κB) is a dimeric transcription factor constituted by two of five protein family members. It plays an essential role in inflammation and immunity by regulating the expression of numerous chemokines, cytokines, transcription factors, and regulatory proteins. Since NF-κB is expressed in almost all human cells, it is important to understand its cell type-, tissue-, and stimulus-specific roles as well as its temporal dynamics and disease-specific context. Although NF-κB was discovered more than 35 years ago, many questions are still unanswered, and with the availability of novel technologies such as single-cell sequencing and cell fate-mapping, new fascinating questions arose. In this review, we will summarize current findings on the role of NF-κB in monocytes and macrophages. These innate immune cells show high plasticity and dynamically adjust their effector functions against invading pathogens and environmental cues. Their versatile functions can range from antimicrobial defense and antitumor immune responses to foam cell formation and wound healing. NF-κB is crucial for their activation and balances their phenotypes by finely coordinating transcriptional and epigenomic programs. Thereby, NF-κB is critically involved in inflammasome activation, cytokine release, and cell survival. Macrophage-specific NF-κB activation has far-reaching implications in the development and progression of numerous inflammatory diseases. Moreover, recent findings highlighted the temporal dynamics of myeloid NF-κB activation and underlined the complexity of this inflammatory master regulator. This review will provide an overview of the complex roles of NF-κB in macrophage signal transduction, polarization, inflammasome activation, and cell survival.